Autological Manifestations of HIV/AIDS Patients - Sopyan Assauri (Jurnal KESANS : Kesehatan dan Sains, 2022)
Human immunodeficiency virus (HIV) / acquired immunodeficiency syndrome (AIDS) infection is a global pandemic. An estimated 34 million people are currently infected with this virus worldwide, two-thirds of whom live in sub-Saharan Africa; 50% are women and 2.5 million are under 15 years old. AIDS is a deadly disease that weakens the body's immune system, leaving the victim vulnerable to life-threatening opportunistic infections, neurological disorders, or unusual malignancies. Approximately 80% of HIV patients are initially infected with ENT symptoms. Manifestations of AIDS in the head and neck area can affect the skin, ear, upper aerodigestive tract, and neck. Objective: To determine the otologic manifestations that occur in patients infected with Human immunodeficiency virus (HIV) / acquired immunodeficiency syndrome (AIDS). Design and Method: Literature-review. Conclusion: Ontological manifestations are signs and symptoms that occur in patients related to the ear and do not require an audiological examination to identify them. There is evidence that 30-50% of adults with HIV/AIDS have hearing loss, with this rate being higher in pediatric patients with HIV. It is often accompanied by symptoms such as ear pain, otorrhea, dizziness, and hearing loss. The current standard of care is to treat people with HIV infection with antiretroviral therapy (ART) as soon as possible, both to improve their own health and to reduce the risk of transmitting HIV to others. In the world, there are 23 million people currently living on ART medication Keyword: Human immunodeficiency virus (HIV), acquired immunodeficiency syndrome (AIDS), manifestation, otologic.